2019
DOI: 10.1002/qj.3446
|View full text |Cite
|
Sign up to set email alerts
|

How confident are predictability estimates of the winter North Atlantic Oscillation?

Abstract: Atmospheric seasonal predictability in winter over the Euro-Atlantic region is studied with an emphasis on the signal-to-noise paradox of the North Atlantic Oscillation. Seasonal hindcasts of the ECMWF model for the recent period show, in agreement with other studies, that correlation skill over Greenland and parts of the Arctic is higher than the signal-to-noise ratio implies. This leads to the paradoxical situation where the real world appears more predictable than the models suggest, with the forecast ense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 71 publications
6
61
1
Order By: Relevance
“…More specifically, it allows for a continuous rather than a discrete representation of the signal. A potential disadvantage of this alternative signal‐to‐noise model is that recent work has suggested that some forecast models used in numerical weather prediction may be overdispersive (Scaife & Smith, ; but see also Weisheimer et al, ; Osman et al, ). If such an overdispersive scenario was the case for the present hindcast ensemble, then this alternative signal‐to‐noise model would offer an unduly pessimistic estimate of S2S forecast skill.…”
Section: S2s Hindcasts Of the Extratropical Circulationmentioning
confidence: 99%
“…More specifically, it allows for a continuous rather than a discrete representation of the signal. A potential disadvantage of this alternative signal‐to‐noise model is that recent work has suggested that some forecast models used in numerical weather prediction may be overdispersive (Scaife & Smith, ; but see also Weisheimer et al, ; Osman et al, ). If such an overdispersive scenario was the case for the present hindcast ensemble, then this alternative signal‐to‐noise model would offer an unduly pessimistic estimate of S2S forecast skill.…”
Section: S2s Hindcasts Of the Extratropical Circulationmentioning
confidence: 99%
“…(), during recent winters there has been a large increase in the variability of the NAO and analysis of hindcasts initialized over a 110‐year period (Weisheimer et al . ) suggests that there is significant variation of over‐ and underconfidence during the 20th century linked to long‐term variability of the global circulation and teleconnections (e.g. O'Reilly, ).…”
Section: Discussionmentioning
confidence: 99%
“…Weisheimer et al . () also see differences in over‐ and underconfidence when they are measured with different diagnostics, and suggest that, when the predictable signal in the hindcasts is too weak, some diagnostics of over‐ and underconfidence are more sensitive to a change in the amplitude of the signal than others. It is important to note, though, that the results of Weisheimer et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations